2010
DOI: 10.3109/08860221003592838
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Oxygen Protects Rat Kidney from Cisplatin Nephrotoxicity

Abstract: Cisplatin (CP) nephrotoxicity is mainly due to reactive oxygen species. Oxygen pre-exposure as a mild oxidative stress may enhance some endogenous defense mechanisms, so its effect on cisplatininduced acute renal failure was investigated in present study.Twenty-four rats were divided into four groups. The O 2 + CP and Air + CP groups were were subjected to i.p. injection of 5 mg/kg cisplatin, and in the Air + Saline and O 2 + Saline groups, saline was injected instead of cisplatin. O 2 + CP and O 2 + Saline gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 39 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…6,12,13 The present study demonstrates that this beneficial effect of oxygen pretreatment also is present in human renal tubular cells. Previously proposed mechanisms which could also explain somewhat the present study findings, is that sub-lethal excess amount of free radicals produced during oxygen pretreatment 29 may act as a mediator for induction of cellular protective agents like antioxidant enzymes, 13 heat shock proteins (Wahhabaghai et al, unpublished data) and probably other endogenous defense mechanisms.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…6,12,13 The present study demonstrates that this beneficial effect of oxygen pretreatment also is present in human renal tubular cells. Previously proposed mechanisms which could also explain somewhat the present study findings, is that sub-lethal excess amount of free radicals produced during oxygen pretreatment 29 may act as a mediator for induction of cellular protective agents like antioxidant enzymes, 13 heat shock proteins (Wahhabaghai et al, unpublished data) and probably other endogenous defense mechanisms.…”
Section: Discussionsupporting
confidence: 67%
“…3,4 Numerous attempts have been made to decrease CP nephrotoxicity, and several substances shown to be protective in cell culture also were found to protect the kidney from damage in vivo. [5][6][7] Many studies support the concept that previous renal injury may protect the kidney against a second insult, and it has been shown that the primary stimulus should not necessarily reach the damage level. 6,8 For example, sub-lethal short ischemic periods may decrease subsequent renal functional or structural injury stimulated by prolonged ischemia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 On the other hand, some evidences suggest that exposure to oxygen prior to Cisplatin therapy may reduce the Cisplatininduced nephrotoxicity in animal model. 10,11 Hypoxia and mitochondrial injury are also implicated in Cisplatin nephrotoxicity. 7 According to our literature review, there is no clinical human study in terms of impact of oxygen therapy before Cisplatin administration on kidney injury.…”
Section: Introductionmentioning
confidence: 99%